(untitled) (Al-Academy, 2018)
The simulation is the oldest theory in art, since it appeared in the Greek aesthetic thought of the philosopher Plato, as we find in many of the thinkers and philosophers over a wide period of time to reach our world today. Our fascination with art in general and design art in particular is due to the creativity and innovations of the artist through the simulation, as well as the peculiarities in this simulation, which give objects signs and signals that may have an echo that sometimes does not exist in their physical reality. The real representation of life and design construction, descriptions of the expression of each of them in the form of intellectual construction and the ideas of productive action between functional and utilitarian, aesthetic, is subject to factors in which the relations are sensual in the recipient the ability to effectively communicate between elements and vocabulary and symbols and their implications, which will positively affect the design process As a whole. The researcher found that there is a weakness in some of the technical formations as an intellectual formulation by following the formal method of simulation. Therefore, the determinants of the problem were identified in their philosophical dimensions between the formal relationship of tradition and the art of design, each taking a different approach to the treatment of ideas. As well as the importance of research in the statement of the need for such studies and the Arab library library culture. With attention to the intellectual dimension of artistic production of simulation and design. In the research aspects, the concepts of simulation theory and artistic opinions were adopted, in which the structure of shapes begins to deal with the subjects designed according to the concepts and concepts of the formal expression in the final output, as well as the approach of the comparative criticism in reaching the results and recommendations through an elected sample and models Do design and modeling to simulate artistically.